Difference scheme for dynamic simulation describing stochastic kinetics of molecules in ceramics - Frishfelds, V.; Madzhulis, I.; Rimshans, J. (Mathematical Modelling and Analysis, 1998)
A conservative and monotonous finite difference scheme is proposed for solving PDE describing the kinetics of molecules in ceramics. Numerical results of computational experiments are presented. First Published Online: 14 Oct 2010